Well-Posedness for the Abstract Blackstock–Crighton–Westervelt Equation - Lizama-Yanez, C (Birkhauser, 2021)
In this paper, an abstract degenerate hyperbolic equation is considered that includes the semilinear Blackstock–Crighton–Westervelt equation. By proposing a new approach based on strongly continuous semigroups and resolvent families of operators, we prove an explicit representation of the strong and mild solutions for the linearized model by means of a kind of variation of parameters formula. Moreover, we show that under nonlocal initial conditions, the existence of a mild solution of the semilinear equation can be established. © 2020, Springer Nature Switzerland AG.